Effects of 10- and 30-minute Hepatic Ischemia on Total Protein, Albumin, Globulin Fractions, and LDH of Male Albino Rates; An Experimental Study - Garib Ismayilova, Shalala; Abaszade, Zumrud; Kazimli, AygunVugar; Taryel Guliyeva, Nigar; Faramaz Khidirova, Hijran; Rauf Abbasova, Maryam; Sahib Alkishiev, Kamil (Archives of Academic Emergency Medicine, 2025)
Introduction: Hepatic ischemia results in the dysrhythmia of the intrahepatic hemodynamics. This study aimed to evaluate the changes occurring in the protein metabolism and serum lactate dehydrogenase (LDH) level after hepatic ischemia and assess the effects of antioxidant therapy in this regard. Methods: In this experimental study (with manipulation of ischemia time and antioxidant therapy) 120 male rats were divided into groups of acute hepatic ischemia; acute hepatic ischemia +antioxidant; chronic ischemia using tetra chloromethane; and sham or intact control to evaluate the changes occurring in the protein metabolism (total protein, albumin, and globulin fractions) and LDH level 3, 7, 15, and 30 days after 10- or 30-minute hepatic ischemia induction and effects of antioxidant therapy in this regard. Results: In the 10-minute ischemia group, total protein decreased to 34.69 ± 2.49 g/L at 3 days, while albumin fell to 12.36 ± 0.85 g/L. The inflammatory response was evident through elevated α1-globulin (9.02 ± 1.50 g/L) and LDH (3476.37 ± 324.89 U/L) at day 3, which gradually normalized by day 30. In the 30-minute ischemia group, the effects were more pronounced, with total protein reaching 54.57 ± 1.93 g/L and albumin 34.33 ± 2.20 g/L at day 3, alongside marked increases in α1-globulin (10.35 ± 1.30 g/L), α2-globulin (3.19 ± 0.43 g/L), β-globulin (8.09 ± 2.27 g/L), γ-globulin (5.64 ± 1.08 g/L), and LDH (2301.44 ± 80.07 U/L). After 10- and 30-minute ischemia, α1, α2, β, and γ globulins as well as LDH level were significantly increased at the post-ischemic recovery. The group that received antioxidant showed significantly lower increases in the globulin fractions and LDH level at 3, 7, 15, and 30 days after the procedure. Conclusion: Based on the findings, 10- and 30-minute acute hepatic ischemia had a profound negative effect on protein metabolism, which was reflected in decreased total protein and albumin, and increased globulin fractions and LDH, indicating the presence of continuous hepatocellular injury and a significant inflammatory reaction. Riditox antioxidant therapy had a consistent, albeit incomplete, hepatoprotective effect, which attenuated these biochemical imbalances.